The Advertising Challenges of the Internet: the strategic perception of Florianópolis agencies - Moraes, Mário Cesar Barreto; Moreira, Mariana Fraga; Kalnin, Guilherme Felipe (Revista de Negócios, 2016)
This research aims to propose strategic actions in order to increase the development of the Internet communication vehicles in the context of Florianópolis from the perception of its advertising agencies, including the factors that influence media buying, the relationship between vehicle and agency and the challenges to be faced to the rise of the internet as advertising media.The research was divided into exploratory stage, in which befits documentary and bibliographic research, and descriptive stage, conducted through in-depth interviews with agency leaders. As a result, separate proposals were structured into four different perspectives regarding the relationship, training, regulation and results of agencies, and observe how major problem the difficulty of training, lack of knowledge of clients and low profitability coming from the internet in Featured advertising environment.